Effect of Danshen for improving clinical outcomes in patients with bladder cancer: a retrospective, population-based study - Chen, Yi-Hsin; Chen, Chih-Tsung; Wu, Han-Ping (Frontiers in Pharmacology, 2023)
Traditional Chinese medicine (TCM) is widely used in healthcare. Danshen has been used in Eastern medicine for the treatment of cancer. This study investigates the association between Danshen use and cardiovascular risks in bladder cancer patients, revealing potential benefits. Patients were selected based on a confirmed diagnosis of bladder cancer. Specific inclusion criteria were set, excluding patients with certain comorbidities or those undergoing specific treatments. Between 2003 and2013, this retrospective, population-based study utilized Taiwan's National Health Insurance data and identified 525 patients with bladder cancer treated with Danshen, 6,419 patients not treated with TCM, and 4,356 patients treated with TCM but not with Danshen. The Cox proportional hazard model was chosen due to its ability to estimate the risks of MACE and mortality while accounting for various confounders. The overall incidence of MACEs in patients with bladder cancer was significantly lower in the Danshen group (5%) than in the TCM (8.1%) and non-TCM (9.9%) groups (p<0.001).The Cox proportional hazard model revealed that patients with bladder cancer treated with Danshen had the lowest risk of MACE (adjusted hazard ratio, 0.56; 95% confidence interval, 0.38-0.84) and all-cause mortality (adjusted hazard ratio, 0.60; 95% confidence interval, 0.44-0.82). Danshen reduces the risk of MACE and all-cause mortality in patients with bladder cancer. Our findings suggest potential benefits of Danshen in bladder cancer patients, warranting further research.